Chronic Social Defeat Stress Up-Regulates Spexin in the Brain of Nile Tilapia (Oreochromis niloticus) - Chor Hong Lim (Nature Portfolio, 2020)
Abstract Spexin (SPX), a neuropeptide evolutionarily conserved from fish to mammals, is widely distributed in the brain and peripheral tissues and associated with various physiological functions. Recently SPX has been suggested to be involved in neurological mechanism of stress. The current study investigates the involvement of SPX in chronic social defeat stress, using male teleost, the Nile tilapia (Oreochromis niloticus) as an animal model due to its distinct social hierarchy of dominant and subordinate relationship. The tilapia genome has SPX1a and SPX1b but has no SPX2. In the Nile tilapia, we localized SPX1a and SPX1b in the brain using in-situ hybridization. Next, using qPCR we examined gene expression of SPX1a and SPX1b in chronically stress (socially defeated) fish. SPX1a expressing cells were localized in the semicircular torus of the midbrain region and SPX1b expressing cells in the telencephalon. Chronically stress fish showed elevated plasma cortisol levels; with an upregulation of SPX1a and SPX1b gene expression in the brain compared to non-stress (control) fish. Since social defeat is a source of stress, the upregulated SPX mRNA levels during social defeat suggests SPX as a potentially inhibitory neuropeptide capable of causing detrimental changes in behaviour and physiology.